Climatic barriers to soft-mobility in winter: Luleå, Sweden as case study. (November 2017) - Chapman, David; Nilsson, Kristina; Larsson, Agneta; Rizzo, Agatino
Highlights: Exploration of the impacts of weather on non-motorised human movement (soft-mobility) in winter. Highlighting of the weather and terrain conditions that act as barriers to soft-mobility in winter. Results that link changing barriers to soft-mobility in winter with climate change. Abstract: Urban form can moderate the effects of weather on human movement. As such, the interrelationship between built environment, weather and human movement is a critical component of urban design. This paper explores the impacts of weather on non-motorised human movement (soft-mobility). Throughout we look at soft-mobility from the citizen's perspective and highlight the barriers to soft-mobility in winter. The aim of this study was to test the traditional pallet of winter city urban design considerations. Those of solar-access, wind and snow management and explore other weather and terrain conditions that act as barriers to soft-mobility in winter. This study is based on survey responses from 344 citizens in the sub-arctic area of Sweden. Outcomes from the research highlight that rain, icy surfaces and darkness are today's most significant barriers to soft-mobility in winter. Results from this study link changing barriers to soft-mobility in winter with climate change. The paper concludes that future urban design and planning for winter cities needs to consider a wider pallet of weather conditions, especially rain.